Empowering Women in Ecclesiastical Spaces: Insights from the World Council of Churches. (Global Journal of Human-Social Science, 2024)
This study delves into the responses of women amidst the dynamic shifts within the ecumenical movement from 1910 to 1948. Two pivotal developments marked the burgeoning presence of women in missions during the early 20th century. The Edinburgh World Missionary Conference of 1910 emerged as a cornerstone event within the ecumenical movement, attracting numerous women missionaries representing diverse missionary societies and church mission boards. Concurrently, the Woman's Missionary Jubilee underscored the fostering of camaraderie among women across First World and Third World churches. These events catalyzed the integration of women into the fabric of Protestant missions, leading to the formation of women's communities and their significant contributions to church establishment, development, and expansion.
Keywords: women; ecumenical; YWCA; WSCF; women’s committee; world council of churches; women’s work for women